Errata - Santos, Karla Priscilla Paulino dos; Lima, Suzinara Beatriz Soares de; Silveira, Lidiana Batista Teixeira Dutra; Soares, Rhea Silvia de Avila; Pozzebon, Bruna Rossarola; Eberhardt, Thaís Dresch (Revista SOBECC, 2022)
***